Scrotal Tongue in Juvenile Oral Pemphigus Vulgaris - Shruthi Madhavi Govindarajulu; Anagha Nair; Praveen Kumar Shanmugam Reddy; Tharayil Kunneth Sumathy (Clinical Dermatology Review)
We report a rare case of oral pemphigus vulgaris (PV) in a 12-year-old boy who presented with fissures on the tongue and erosions on the buccal and lingual mucosa of 8-month duration. Tzanck smear from the buccal mucosa revealed acantholytic cells. Biopsy and direct immunofluorescence from the tongue were consistent with PV. After starting immunosuppressive treatment, the patient’s erosions and fissures significantly improved. The distinctive scrotal tongue appearance linked to adolescent oral PV makes this case noteworthy.